Implementation of Android-Based Hair Color Media in the Double Application Hair Coloring Instruction - Witdarsih , Witdarsih; Qudus, Nur; Ikhsani, Ade Novi Nurul; Supraptono, Eko (Universitas Negeri Semarang, 2025)
The issue addressed in this research is the low competency of students in understanding the material of double application hair coloring, with approximately 70% of students achieving learning outcomes below the established competency standard. Therefore, a more user-friendly, engaging, and easily understandable hair color media is needed for students in its application. This study aims to: Develop Android-Based Hair Color Media as a learning tool that meets the criteria for an effective learning medium, Analyze the feasibility of the Android-Based Hair Color Media based on assessments from media and content validators, Analyze the practicality of the Android-Based Hair Color Media based on feedback from students and peers (teachers), and analyze the effectiveness of the Android-Based Hair Color Media in improving cognitive abilities. This is a development research (R&D) study. The development model used is the ADDIE model. The results show that: The design of the Android-based hair color media meets the requirements, The Android-based hair color media is feasible to be used as a learning tool, The Android-based hair color media is practical for use in teaching, and The Android-based hair color media is effective in enhancing cognitive abilities, as evidenced by the improved learning outcomes. The conclusion of this study is that the developed hair color media design meets the criteria, is feasible, practical, and effective in improving cognitive skills. The benefit of this research is that the Android-based hair color media is feasible, practical, and effective in enhancing cognitive abilities.